8 basic building blocks rebuilt - Senathirajah, Pathman; VStudios ([S.l.] : VStudios, 2008)
Presents eight basic practices necessary for a networker to succeed. This videos combines personal techniques, strategies, and methodologies for you to effectively work on your business and build your network
Title from title screen
DVD format
Keywords: Multilevel marketing; Direct marketing